RESEARCH ON THE INFLUENCE OF PROFESSIONAL IDENTITY AND LEARNING MOTIVATION OF VOCATIONAL EDUCATION ARCHITECTURE MAJOR STUDENTS ON LEARNING ENGAGEMENT - Kaijun Du; Krittavit Bhumithavara (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This research is situated within the backdrop of China's rapidly expanding higher education, where the quality of higher education has become a focal point. Historically, higher education quality evaluation has emphasized external factors such as teaching staff and facilities. However, with the evolution of research, there has been a shift towards focusing on students as the core. Learning engagement, as a key indicator of students' growth and higher education quality, has drawn significant attention. Given its low-to-medium level among most students, improving it has become an urgent matter. The study focuses explicitly on architecture students in vocational education, exploring the relationships among professional identity, learning motivation, and learning engagement. The research variables include personal factors, professional identity, learning motivation (subdivided into internal and external motivation), and learning engagement. The study uses students from Sichuan College of Architectural Technology and Zhejiang College of Construction as the sample, selected using random and stratified sampling methods. The research holds great significance. It aims to uncover the internal mechanisms of students' learning behaviors, offering theoretical and practical guidance for enhancing the quality of vocational education and promoting students' all-round development. Proposed hypotheses include the significant influence of personal factors, the positive impact of professional identity, and the significant influence of learning motivation on the learning engagement of architecture students. Although the research conclusion is not explicitly stated in the given text, the study aims to provide insights into improving architecture students' learning engagement in vocational education, thereby potentially enhancing the quality of vocational education in the architecture field.